TWINS Observations of the Dynamics of Ring Currents Ion Spectra on March 17 and October 7, 2015. Issue 2 (9th February 2021) - Shekhar, S.; Perez, J. D.; Ferradas, C. P.
Abstract: Direct comparisons between RBSP (Van Allen Probes or Radiation Belt Storm Probes) and TWINS (Two Wide‐angle Imaging Neutral‐atom Spectrometers) for the main phase of two storms, March 17 and October 7, 2015, showed agreement between the in situ ion measurements and the ion spectra from the deconvolved energetic neutral‐atom (ENA) measurements, except when O + ions were significant. Spatial evolution of individual energy peaks in the ion spectra is studied using TWINS data. O + ions are seen to result in intense peaks at 5–10 keV/amu in the TWINS ion spectra. These ion populations are confined to low L shells (L < 5) and localized in the premidnight sector. When H + ions are significant, the low energy peaks (<25 keV/amu) are found to be less intense than the high energy peaks (>25 keV/amu), located at L > 4 and localized within the premidnight sector. During times of rapidly varying AE indices, two spatially distinct peaks, between 3–5 R E and 6–8 R E, are observed for the ions with energies >25 keV/amu. The outer peak appears for a few hours and fades while the inner peak is more stable. These structures are found to be consistent with particle injections observed in the RBSP data. When double peaked structures are swept off, low energy ions accumulate in the premidnight to midnight sectors whereas high energy ions are located premidnight to postmidnight sectors. Faster drift orbits of >25 keV/amu ions may cause this kind of distribution. Key Points: TWINS ion spectra agree with RBSP in situ H + ion spectra during main phase of geomagnetic storms on March 17 and October 7, 2015 O + ions contribute to peaks at energies 5–10 keV/amu in TWINS ion spectra which spatially extend to L < 5 and in the premidnight MLT sectors Spatial dynamics of TWINS ion spectra reveal signatures of varying convection rates, particle injections, and energy‐dependent drift